VON HIPPEL-LINDAU SYNDROME: ASPECTS OF TREATMENT AND MANAGEMENT. CASE REPORT AND LITERATURE REVIEW - I. I. Larina; N. M. Platonova; E. A. Troshina; A. A. Roslyakova; D. G. Belzevich; L. S. Selivanova; M. Yu. Ukina; L. V. Nikankina; N. M. Malysheva; A. N. Tyulpakov; L. D. Kovalevich (SINAPS LLC, 2019)
The steadily growing interest in studying of endocrine genetics is driven not only by the search for new pathologies but also by the most pressing need to develop methods for early diagnosis, treatment and management of patients. Though 20% of all the patients with von Hippel-Lindau syndrome do not have a family history of the disease; a genetic basis is a natural characteristic of the disease and determinates a phenotype. Despite the nonaggressive course, in general, a relative unpredictability of the syndrome signs onset and the lack of regular monitoring can increase the risk of surgery complications and cause a disability at a young age. The presented clinical case shows the need for a multidisciplinary approach to management of the patients with von Hippel-Lindau syndrome.